PELATIHAN DIVERSIFIKASI PRODUK KEPITING KERACA BERBASIS ZERO WASTE DI UKM DESAKITARA - Novi Luthfiyana; Stephanie Bija; Heni Irawati; Andi Ramadani; Anhar Rozi (Jurnal Marine Kreatif, 2021)
Keraca crabs are a small genus of portunidae that the community has begun to develop into food products. To increase the economic value and reduce the accumulation of processing industrial waste, keraca crab products can be carried out with the concept of zero waste. This activity aims to increase knowledge, skills and increase production through diversification of processed crabs with the concept of zero waste. The method of this activity begins with the stages of preparation, counseling and socialization, training, evaluation and follow-up. Training on the diversification of crab products was carried out with partners, namely UKM Desakitara. The results of this activity are able to increase partner's knowledge and technology, improve partner skills in processing Keraca crab waste into nutritious food products and be able to produce two new products, namely petis and ikat crackers. The new products produced are able to increase partner production.